(untitled) (Journal of Medical & Health Sciences Review, 2025)
Data analytics is the process of using statistical, computational and machine learning algorithms to describe patterns, trends and relationships in data.The concept of data analytics its development major techniques and the broad spectrum of the implications of its use in different spheres. The data analytics a necessity in making sense of this huge volume of information to be used in making decisions. It is a central role in assisting businesses to maximize operations, predict trends, customize services and discover new prospects. It has become crucial to decipher the basics of data analytics and its implementation in real life. An exploratory literature review study was utilized to review the current scholarly and industry research on information on data analytics frameworks and applications. The articles were peer-reviewed journal articles, conference papers and industry reports published between 2015 and 2024. The case studies in industries like healthcare, banking and retail were examined to get an idea about the practical implementation and the result of data analytics projects. Data analytics has transformed how organizations perceive and act on their surroundings. The advanced analytics and data-literate individuals will increase as data keeps expanding in volume and complexity. The future of data analytics might be in real-time analytics, artificial intelligence integration, data privacy challenges, and other emerging areas which should be topics of future research to completely unleash the power of data analytics in a sustainable and responsible fashion.